Analysis of Damage Levels and Maintenance Using IRI on the Pandaan-Malang Toll Road - Ahmad Abdul Aziz, Hafif; Ayu Kusuma Dewi, Vita; Nurita Prameswari, Putri; Izatullilah (Rekayasa Sipil, 2025)
Good road conditions are critical in ensuring the comfort, safety, and efficiency of road users' journeys. The Pandaan–Malang Toll Road, as a strategic infrastructure with a traffic volume of 43 million vehicles per year, faces challenges related to the degradation of road surface quality due to traffic dominated by light vehicles. However, previous studies have not extensively integrated the relationship between vehicle volume and the International Roughness Index (IRI) values on a segmental basis as a basis for maintenance evaluation. This study aims to analyze the IRI conditions of five segments of the Pandaan–Malang toll road during the period 2022–2024 and recommend maintenance strategies based on IRI classification in accordance with Ministry of Public Works and Public Housing Regulation No. 47 of 2015. The method used is quantitative with secondary data analysis of IRI values from PT Jasa Marga Pandaan–Malang based on RoadRoid Survey Application and processed using Microsoft Excel. The results show that the average IRI value in 2024 is 3.66, classified as Good, but Segments I and II classified as Fair with values >4 and require periodic maintenance. Other segments can still be maintained through routine maintenance. This study concludes that the IRI values show a stable trend but have the potential to increase without planned maintenance. Future research is recommended to examine the integration between IRI, PCI, and traffic load to develop a more comprehensive and applicable road damage prediction model.